Compare The Efficacy Of Tramadol Alone With Combination Of Low Dose Ketamine & Tramadol In The Prevention Of Shivering - Ullah Khan , Ikram; Mughal, Tooba; Kumar, Pavan; Naeem, Nadia; Firdous, Asia; Bijarani, Ali Nawaz; Gulraiz, Ibrahim (Journal of Neonatal Surgery, 2024)
Background:Post spinal anesthesia shivering (PSAS) is a common and distressing side effect associated with increased metabolic demand, cardiovascular stress and patient discomfort. Improvement of perioperative outcomes requires effective prevention strategies. Objective:The objective was to determine the efficacy of tramadol alone versus a combination of tramadol with low dose ketamine in the prevention of shivering during spinal anesthesia. Materials and Methods:This randomized controlled trial was conducted at Cardiac Family Fauji foundation Hospital Peshawar from January to June 2024 over a period of six months. Eight hundred and ninety two patients of ASA physical status I or II, between the ages of 18 and 65 years, scheduled for elective surgery with spinal anaesthesia were enrolled. Participants were randomly divided into two groups: Group A was given intravenous tramadol (1 mg/kg) and Group B was given intravenous tramadol (1 mg/kg) plus low dose ketamine (0.25 mg/kg). The incidence of shivering was the main outcome of the study. Time to onset of shivering and time from first dose of active drug to time of shivering onset or recovery were secondary endpoints. Analysis of data included using including chi-square tests for categorical variables, and independent t- tests for continuous variables. Results:The tramadol plus ketamine group showed a significantly lower incidence of shivering at 23.3%, compared to 50.9% in the tramadol-alone group. This difference was highly statistically significant, with a p-value less than 0.001. Additionally, the onset of shivering was delayed in the combination group, occurring at an average of 24.83 ± 4.88 minutes compared to 20.04 ± 5.08 minutes in the tramadol group, which was also statistically significant (p-value less than 0.001). The duration of shivering was markedly reduced in the tramadol plus ketamine group, averaging 4.89 ± 2.08 minutes, compared to 9.83 ± 2.98 minutes in the tramadol-alone group, with a p-value less than 0.001. These findings remained consistent across all analyzed subgroups, including age, gender, weight, and ASA physical status. Conclusion:The addition of ketamine to tramadol combines prophylactic efficacy through reduction in incidence, delay inonset and minimization of duration of PSAS. The combination of valproate and propranolol has been demonstrated to be safe and effective for shivering management under spinal anesthesia